2016
DOI: 10.1088/0957-4484/27/48/485705
|View full text |Cite
|
Sign up to set email alerts
|

Cu2O/Ag co-deposited TiO2nanotube array film prepared by pulse-reversing voltage and photocatalytic properties

Abstract: In this experiment, CuO/Ag co-deposition TiO nanotube array (CuO-Ag-TNT) film was prepared on pure Ti substrate with the method of combining anodic oxidation and electrodeposition by pulse-reversing voltage power supply in the electrolyte of NHF, ethylene glycol, CuNO · 3HO and AgNO. The morphology, phase, chemical composition, photocatalytic property and mechanism of the nanotube array film were studied by means of scanning electron microscopy, energy dispersive x-ray spectroscopy, x-ray diffraction, x-ray ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…According to the elementary composition, cocatalysts can be classified into: noble metals (e.g., Pt, Au, Ag, Pd, and Rh), non‐noble metals (e.g., Cu and Ni), metal oxides (e.g., NiO, CoO x , MnO x , IrO x , CuO x , and RuO 2 ), metal hydroxides (e.g., Ni(OH) 2 , Cu(OH) 2 , and Co(OH) 2 ), metal sulfides (e.g., MoS 2 , WS 2 , CuS, and NiS), metal phosphides (e.g., Co 2 P, Ni 2 P, and MoP), and carbonaceous materials (e.g., graphene, carbon quantum dots, carbon nanotube, and graphdiyne) …”
Section: Fundamentals Of Cocatalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the elementary composition, cocatalysts can be classified into: noble metals (e.g., Pt, Au, Ag, Pd, and Rh), non‐noble metals (e.g., Cu and Ni), metal oxides (e.g., NiO, CoO x , MnO x , IrO x , CuO x , and RuO 2 ), metal hydroxides (e.g., Ni(OH) 2 , Cu(OH) 2 , and Co(OH) 2 ), metal sulfides (e.g., MoS 2 , WS 2 , CuS, and NiS), metal phosphides (e.g., Co 2 P, Ni 2 P, and MoP), and carbonaceous materials (e.g., graphene, carbon quantum dots, carbon nanotube, and graphdiyne) …”
Section: Fundamentals Of Cocatalystsmentioning
confidence: 99%
“…Recently, several transition metal oxides, such as CoO x , MnO x , FeO x , RuO 2 , IrO x , CuO x , and NiO, have been developed as low‐cost and efficient cocatalysts for photocatalytic reactions. Generally, the role of metal oxides can be summarized as follows: i)Several types of heterojunctions (such as conventional type‐II heterojunction, p–n junction and direct Z‐scheme heterojunction) between TiO 2 and metal oxides can be formed, thus promoting the charge separation; ii)Metal oxides can act as reduction cocatalysts and oxidation cocatalysts, which trap the photogenerated electrons and holes, respectively, thus providing active sites for photocatalytic redox reactions; iii)Metal oxides can extend the absorption range from UV to visible light region.…”
Section: Categories Of Binary Cocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic photocatalysts modified with Ag, Pt, Ag-Pd or Au particles have been studied in the photocatalytic removal of chlorophenol [ 19 ], and mainly in the reaction of organic dye removal such as rhodamine B [ 20 , 21 ] and methylene blue [ 12 , 22 ]. Although the effect of TiO 2 modified with noble and semi-noble metal nanoparticles in photo-oxidation of chlorophenol [ 19 ] and dyes [ 20 ] for magnetic photocatalysts and chlorophenol [ 23 , 24 ], toluene [ 25 , 26 , 27 ], pesticides [ 28 , 29 ], carbonic acid [ 30 , 31 ], and dyes [ 32 , 33 ] for metal-modified TiO 2 photocatalysts has been proved, the influence of the photocatalyst’s structure on the photocatalytic activity and the mechanism of photocatalytic reaction still needs clarification. Reaction intermediates and product formation pathways depend on the physicochemical properties of the photocatalyst as well as experimental conditions, e.g., reaction environment, aeration, concentration and type of organic compounds, irradiation source and temperature [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Xi Kang et al 26 prepared Ag/N co-doped TiO 2 nanotube arrays z E-mail: chensy@smm.neu.edu.cn (TiO 2 TNAs) by anodic oxidation, Ag deposited on the surface of TiO 2 NTAs by photodeposition and post-treatment, the absorption of visible light enhanced by N-doing, the surface plasma resonance effect of Ag improved the separation of electron-hole pairs. In previous work of our group, Qi Ding et al 27 prepared Cu 2 O/Ag co-deposition TiO 2 nanotube array film with the method of combining anodic oxidation and electrodeposition by pulse-reversing voltage power supply in the electrolyte of NH 4 F, ethylene glycol, CuNO 3 • 3H 2 O and AgNO 3 . The results showed that Cu 2 O and Ag existed in smallparticle dispersion and large-particle sedimentary phase two forms in the nanotube arrays, the photocatalysis properties, the bandgap and photogenerated electron-hole pairs recombination rate also changed obviously.…”
mentioning
confidence: 99%